Pseudo-Cyril of Jerusalem on the life and the passion of Christ : a Coptic apocryphon - Broek, R. van den. (Vigiliae Christianae, Supplements, 2013)
Pseudo-Cyril of Jerusalem's Coptic homily On the Life and the Passion of Christ is in fact a collection of apocryphal stories. Roelof van den Broek offers a critical edition of this text, with introduction, translation and notes. The text provides information about the worldly crafts of the apostles and Jesus' external appearance; it also contains a peculiar chronology of Holy Week (implying that Jesus was arrested on Tuesday evening) and a long story about Pilate's role in the trial of Jesus. The latter contains, int. al., letters by Pilate and Herod, discussions between Pilate and Jesus during a dinner they had together, and a description of the dreams of Pilate and his wife Procla and their explanation by Jesus.